Mindfulness-Based Approaches to Foreign Language Anxiety in Arabic Speaking Instruction: A Case Study at Madrasah ‘Aliyah - Khozainul Mustafidah; Anyes Lathifatul Insaniyah (Postgraduate of IAIN Metro Lampung Indonesia, 2026)
This study addresses Foreign Language Anxiety (FLA), a common issue in language learning, particularly in Arabic instruction at Madrasah Aliyah Raudlatut Tholabah Banyuwangi, where students often experience anxiety and fear of making mistakes while speaking Arabic. The purpose of this study is to explore the use of mindfulness techniques to reduce FLA and enhance language learning. Using a qualitative descriptive approach and a case study design, data were collected through observations, interviews, and documentation. The teacher applied mindfulness practices such as focused breathing, self-awareness reflection, and attention regulation exercises to help students manage anxiety. Positive feedback was provided, and reprimanding students was minimized to reduce fear during speaking activities. The results show that mindfulness significantly improved students’ confidence and participation in Arabic speaking tasks. Students who were initially anxious became more actively engaged in learning. Mindfulness not only reduces emotional tension but also strengthens the positive relationship between students and the teacher. This study highlights the novel application of mindfulness in Arabic language classrooms. It is suggested that mindfulness be integrated into language teaching practices, with further research needed to explore its long-term effects and individual differences in its effectiveness.